14th European Conference on Thermoelectrics 20-23 September 2016, Lisbon, Portugal Preface. (2018) - Gonçalves, A.P.; Lopes, E.B.; Costa, F.M.; Brito, F.P.; Ferreira, I.; Gonçalves, L.M.
Abstract: We are very pleased to introduce the Conference Proceedings of the 14th European Conference on Thermoelectrics, ECT2016, which contains the written version of important contributions presented during the conference. The European Conferences on Thermoelectrics are high quality scientific forums promoted by the European Thermoelectric Society (ETS) that offer open and informal discussions on Thermoelectrics. All aspects on Thermoelectrics, from materials design, synthesis, characterization to application issues, modules and simulations, are contemplated on these conferences.